Volition in Violation of Copyright - Nimmer, David (The Columbia Journal of Law & the Arts, 2019)
Many recent copyright infringement cases have focused on the question of volition. As contentious as the matter has become in current copyright doctrine, the issue is relatively new. From the passage of the first Copyright Act in 1790 forward, U.S. copyright cases devoted no discussion to the issue. Two centuries later, however, the advent of the Internet raised this issue, among so many others. Nothing is totally new under the sun. As far back as enactment of the 1976 Act, concern was expressed lest telephone companies be ensnared in liability, to the extent that their facilities were used in the retransmission of cable signals. Congress adopted the “passive carrier” exemption, releasing from liability those “whose activities with respect to the secondary transmission consist solely of providing wires, cables, or other communications channels for the use of others.” That provision was necessary as telephone companies risked liability in its absence. Nobody at the time raised lack of “volition” as even a theoretical defense to that imputation. Decades later, with the advent of the Internet and online services, those same considerations multiplied along with the explosion of new ways to use “wires, cables, or other communications channels.” This Article began as the 32d Annual Horace S. Manges Lecture, delivered at Columbia Law School on April 1, 2019.